The presentation of history on Wikipedia or the desire for constancy in the midst of endless change - Lorenz, Maren (Dějiny – teorie – kritika, 2014)
In her study, Maren Lorenz focuses on the phenomenon of the online encyclopedia Wikipedia. She briefly summarizes the development since its inception in 2000 or 2001, and examines in detail the form of entries related to historical sciences. It analyses the politically motivated manipulation of many entries and their ideologisation, but also looks at the procedures that have been developed to control the editing of texts by users of the encyclopaedia. Nevertheless, Lorenz tends to discourage the use of Wikipedia by pointing out its only apparent informational stability and the problematic quality of its treatment of many, mainly minority, topics.